EXPLORING THE IMPACTS AND CHALLENGES OF MOUNTAIN CLIMBING AS PERCEIVED BY THE LOCAL TOUR GUIDES - Camarador, Rhene; Camarador, Lisa; Cruz, Lualhati Dela (International Journal of Psychosocial Rehabilitation, 2020)
Mountain climbing as part of tourism industry is one of the fastest growing opportunities that create jobs, provide services and products to support visitors and the local community. This study ascertained the impact and challenges of mountain Climbing encountered by the local tour guides. Descriptive method of research was employed in the study. Using researcher-made questionnaire in data gathering and simple random sampling technique, the study involved 170 local tour guides in Brgy. San Rafael, Rizal, Philippines. Frequency, weighted mean, percentage, t-test, and one-way ANOVA were the statistical tools employed in analysing all gathered data. Results revealed that the local tour guides have greater positive perception of the economic and socio-cultural impacts of mountain climbing. On the other hand, most of the respondents disagree that mountain climbing may results to soil degradation, can cause natural hazards, causes pollution, and can cause destruction of natural vegetation. Findings also showed that the most common challenges experienced by the local tour guides were maintaining the cleanliness of the community and preservation of their own culture and traditions. There is a significant difference on the perception of the respondents on the economic impact of mountain climbing when grouped according to sex and number of tour guiding years. In terms of ecological impact, respondent’s perception also varies significantly when grouped according to age. It is suggested that the tour guide association develop community-based mountain climbing tourism program that will strengthen the economic impact without sacrificing socio-cultural and ecological development of the community.